1988
DOI: 10.1007/bf01589405
|View full text |Cite
|
Sign up to set email alerts
|

Dual coordinate step methods for linear network flow problems

Abstract: We review a class of recently-proposed linear-cost network flow methods which are amenable to distributed implementation. All the methods in the class use the notion of e-complementary slackness, and most do not explicitly manipulate any "global" objects such as paths, trees, or cuts. Interestingly, these methods have stimulated a large number of new serial computational complexity results. We develop the basic theory of these methods and present two specific methods, the e-relaxation algorithm for the minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 31 publications
1
79
0
Order By: Relevance
“…For integer data, it can be shown that the worst-case running time of the auction algorithm using scaling and appropriate data structures is O nA log(nC) ; see [BeE88], [BeT89]. Based on experiments, the running time of the algorithm for randomly generated problems seems to grow proportionally to something like A log n or A log n log(nC).…”
Section: -Scalingmentioning
confidence: 99%
See 4 more Smart Citations
“…For integer data, it can be shown that the worst-case running time of the auction algorithm using scaling and appropriate data structures is O nA log(nC) ; see [BeE88], [BeT89]. Based on experiments, the running time of the algorithm for randomly generated problems seems to grow proportionally to something like A log n or A log n log(nC).…”
Section: -Scalingmentioning
confidence: 99%
“…The complexity of the scaled version was first studied in [Gol87], where particularly favorable polynomial running time estimates were derived; see [BeE87], [BeE88], [GoT90] for additional results along these lines.…”
Section: Extension To Asymmetric Assignment Problemsmentioning
confidence: 99%
See 3 more Smart Citations